Implementasi Pembelajaran Al-Qur’an di TPQ Al-Anshary Kunciran Indah Pinang, Kota Tangerang - Almaydza Pratama Abnisa (PT. Penerbit Tiga Mutiara, 2024)
Learning is a process of improvement for everyone, especially teachers in guiding their students to gain maximum experience in achieving learning goals, both in learning the Koran. The purpose of writing is to describe the application of Al-Qur’an learning at TPQ Al-Anshary. This research method is qualitative, namely research in the field. Descriptive research in collecting information on the symptoms obtained. Data collection techniques use field observation methods, documentation and interviews. The results of the research are the implementation of Al-Qur’an Learning Methods at TPQ Al-Anshary following the directions implemented by the institution. The application of learning methods is carried out through several activity strategies, namely opening activities, core activities and closing activities. The opening activity begins with jointly reciting the Al-Fatihah letter and reciting Asamul Husna, as well as the core activity using the classical method, and finally the closing activity which ends with carrying out an evaluation of each individual student and ending with reading a prayer.